Joseph Raz: In Memoriam (1939–2022) - M. A. Belyaev (Теоретическая и прикладная юриспруденция)
The article is dedicated to the memory of a major thinker in the field of moral, political and legal philosophy Joseph Raz, the author of a number of influential works on the problems of political authority, the unity and separation of morality and law, the system of political values, private autonomy and the rule of law.